The capacity and effectiveness elimination domestic animals allergens: myths and realities - A. N. Pampura; N. B. Migacheva; E. E. Varlamov; A. I. Asmanov (Медицинский вестник Юга России, 2020)
At present, sensitization to airborne allergens in domestic animals is absolutely rightly considered one of the key risk factors for the development of allergic rhinitis and bronchial asthma, as well as largely determines the development of severe forms of atopic dermatitis and respiratory allergosis. Of particular importance is the fact that, unlike other triggers, the elimination of allergens in domestic animals is often associated with internal resistance from patients. Various aspects of this problem are associated with a large number of baseless statement that lead to inadequate prevention and therapy, as well as negatively affecting the social activity of patients and their families. The article presents the current data on the prevalence of sensitization, the properties and clinical significance of the allergens of domestic animals, outlines approaches to conducting elimination activities.